2013
DOI: 10.5513/jcea01/14.2.1243
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature for development time, fecundity and reproduction on some ornamental aphid species

Abstract: The development time, survivorship and reproduction of the Sarucallis kahawaluokalani (Kirkaldy),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Nevertheless, the average immature development time (from the first nymphal stage up to the post-reproductive adult) was 25.7 days for A. gossypi and 24.8 days for M. persicae. These values were similar in our study, since temperature [33] and host plant conditions [34] affect the length of the development of aphids. Both species showed four nymphal stages, as found by Dixon et al [27], lasting between 1.1-1.5 days, on average.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the average immature development time (from the first nymphal stage up to the post-reproductive adult) was 25.7 days for A. gossypi and 24.8 days for M. persicae. These values were similar in our study, since temperature [33] and host plant conditions [34] affect the length of the development of aphids. Both species showed four nymphal stages, as found by Dixon et al [27], lasting between 1.1-1.5 days, on average.…”
Section: Discussionsupporting
confidence: 89%
“…Temperature, as an important ecological factor, has a significant impact on the development duration, fecundity and population dynamics of insects (Campbell et al ., 1974; Özder and Ozgur, 2013; Cao et al ., 2018). A large number studies have shown that the developmental duration of insects shortens with the increase of temperature over the appropriate temperature range (Cui et al ., 2018; Abu Alloush, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The best indicator to measure the relationship between insect population growth and the temperature is intrinsic growth rate, which can generally reflect the effects of temperature on insect development, reproduction and survival. Typically, the intrinsic growth rate of aphid population is the highest in the temperature range of 25–30°C (Gilbert and Raworth, 1996; Özder and Ozgur, 2013), such as Schizolachnus pineti in 24–36°C (Holopainen and Kainulainen, 2004) and Cinara pinea in 21°C (Shao et al ., 2017). In this study, the intrinsic growth rate of C. cedri is the highest at the temperature of 20°C.…”
Section: Discussionmentioning
confidence: 99%
“…The oleander aphid Aphis nerii is an important invertebrate herbivore of milkweed that shows strong seasonal trends in population dynamics (Smith et al 2008). Aphids are phloem feeders and reproduce asexually through viviparous parthenogenesis (Powell et al 2006), with nymphs reaching sexual maturity in 7–10 days (Özderl and Saǧlam 2013). Aphids migrate north each spring, arriving on plants in our study area (southern Ontario) approximately 9–10 weeks after milkweed germination.…”
Section: Methodsmentioning
confidence: 99%